SEKOLAH MENENGAH KEJURUAN (SMK) JURUSAN PERTANIAN SISTEM BOARDING DI KABUPATEN KLATEN DENGAN KONSEP GREEN ARCHITECTURE - Oyong Satriakusuma; Suparno Suparno; Samsudi Samsudi (Universitas Sebelas Maret Surakarta, 2014)
Abstract: Designing vocational school of department of agriculture in Klaten motivated by the National Education Department policies in order to achieve the ideal composition between the SMA and SMK 33:67 percent, demand for labor vocational graduates are relatively many, and the fact that there are opportunities in designing classrooms better than the standards set at this time. The problem is how to formulate the concept of vocational Department of Agriculture as a place that is able to accommodate a variety of activitis (teaching,laboratory stuff, sports, etc), and how to design forms an ideal class corresponding to the ergonomics of students, where the facility is located in Klaten by using the concept of green architecture in designing buildings. The method used is the method of architectural design, which begins with problem tracking, data collection and information, analysis approach to the concept, and synthesis of data. School is expected to meet the criteria for green architecture by manipulating the building in such a way so as to reduce energy use in operating the building. Keyword: ergonomics of students, green architecture, energy saving